Third Age Men’s Experience of Fashion and Clothing: An Interpretative Phenomenological Analysis - Sadkowska, Anna; Wilde, David; Fisher, Tom (Age, Culture, Humanities: An Interdisciplinary Journal, 2015)
This paper is set within the context of the current shift in focus around aging from an objective to a subjective stance, placing the emphasis on individuality (Bennett and Hodkinson; Powell and Gilbert) and resulting in the emergence and development of cultural gerontology. Human biographies have the potential to be interpreted through the relationships between personal and structural factors, and individual and collective experiences. Fashion and clothes, as communicators and mediators between self and society (Entwistle; Craik) can therefore be seen as key factors in understanding aging identities. Contemporary research on fashion and aging concentrates mainly on older women (Twigg). Whilst this research has told us much about how aging women experience fashion, it excludes the parallel considerations of aging men. This paper addresses this gap by presenting research that investigates how older men negotiate their aging bodies through the media of clothing and fashion. Data were collected via in-depth, semi-structured interviews with fve older men and were analyzed using Interpretative Phenomenological Analysis (IPA). The fndings reveal the experience of fashion and clothing of fve older men who, during their lives, have actively engaged with fashion, considered in the contexts of time, space, and “others” (Kaiser).